The Neuroscience of Learning and the Somatic Poiesis of Architecture - Martínez Vitor, Cesar Fortunato; Salva-Pérez, Saory Shirley (Estoa. Journal of the Faculty of Architecture and Urbanism, 2021)
The neuroscience of learning is linked to the somatic poiesis of architecture. Pedagogy and didactics address this aspect during the professional training of the architect. Documentary grounded theory with a hermeneutic approach and transactional temporality was used for the demonstration. Data were collected using intertextual sheets applied to the neuroscience theory of learning and somatic poiesis of architecture. The outcome demonstrated that emotion and feeling of learning are related to the somatic deliberation of architecture in a distinctive pattern: problems generate an affective reaction in emotions, from which feelings conceptualize perceptions. Therefore, this condition of perception triggers the rejection or acceptance of the current architectural project influencing decision-making. The final conclusion was that, the relationship between the neuroscience of learning and the somatic poiesis of architecture affects the learning process, and the decision-making of the architectural project is based on emotion, feeling, deliberation and intuition.